Implementation of Inclusive Teaching for Children with Special Needs: An Educational Psychology Perspective - Izzati, Khofifah Nurul; Yeni, Putri; Takahashi, Haruto; Santos, Luis (Darussalam: Journal of Psychology and Educational, 2025)
Education is a basic need for every human being to ensure that their life becomes more dignified. Therefore, the state has an obligation to provide quality educational services for every citizen without exception, including those who have different abilities (disabilities ) as regulated in the 1945 Constitution Article 31 paragraph 1. Education of children with special needs is a challenge in the world of education, because not all schools are willing to accept children with special needs in their educational environment. The implementation of inclusive education for children with special needs must be able to create a friendly, fun, flexible environment that can foster self-confidence in students and educators who have special abilities. The reality on the ground in the implementation of inclusive education is that not everything is in accordance with implementation guidelines, both in terms of student conditions, teacher qualifications, supporting infrastructure, parental support, as well as support from central and regional governments. Basically, the implementation of inclusive education for children with special needs is still a phenomenon.